Comparison of the effects of different lipopolysaccharides on the serum bactericidal reactions of two strains of Escherichia coli. - Allen, R J (1981)
The serum killing of Escherichia coli ML308 225 and PB94 was inhibited by lipopolysaccharide extracted from either organism, but not by lipopolysaccharide from three pathogenic Enterobacteriaceae.